Thermo-economic analysis and multi-objective optimization of polygeneration system based on advanced adiabatic compressed air energy storage system. (1st February 2021) - Jiang, Runhua; Cai, Zhuodi; Peng, Kewen; Yang, Minlin
Highlights: A comprehensive mathematical model of polygeneration system is built. Thermo-economic analysis and comparison for two types of system is performed. Compression/expansion stages are the critical factor to determine the system type. There is an optimal heat exchanger effectiveness to make performance best. Multi-objective optimization considering three objective functions is employed. Abstract: An advanced adiabatic compressed air energy storage (AA-CAES) system can operate as a polygeneration system, which stores power from renewables or the grid at off-peak periods and releases power, heating load and cooling load to users at peak periods. According to the energy forms produced by AA-CAES system, it can be categorized as either a cogeneration system (producing power and heating load simultaneously) or a trigeneration system (producing power, heating load and cooling load simultaneously). In this study, a comprehensive mathematical model of polygeneration system based on AA-CAES system is established. Thermo-economic analysis and comparison of cogeneration/trigeneration system based on AA-CAES system are carried out, and the relationships between the type of AA-CAES system with the number of compression/expansion stages and parameters of the system are revealed. Multi-objective optimization considering three objective functions is used to determine the optimal design for two types of AA-CAES systems. When there are two compression stages and two expansion stages, the performance of cogeneration system is optimal, and the round trip performance coefficient RTPC, exergy efficiency η ex and annual total cost saving ratio ACSR are 0.898, 0.68 and 0.258, respectively. When there are three compression stages and one expansion stage, the performance of the trigeneration system is optimal, and RTPC, η ex and ACSR are equal to 1.057, 0.555 and 0.134, respectively. This study will provide guidelines for the design of polygeneration system based on AA-CAES system, which can be widely applied in distributed energy systems to improve the off-design performance.